2022
DOI: 10.3389/fonc.2022.982948
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of lenvatinib combined with camrelizumab plus transcatheter arterial chemoembolization for unresectable hepatocellular carcinoma: A two-center retrospective study

Abstract: ObjectivesTo compare the safety and efficacy of lenvatinib (LEN) combined with camrelizumab plus transcatheter arterial chemoembolization (TACE-LEN-C) and TACE combined with LEN (TACE-LEN) in patients with unresectable hepatocellular carcinoma (uHCC).MethodsEighty-three patients with uHCC treated with TACE-LEN-C or TACE-LEN from September 2018 to May 2021 were enrolled in this retrospective study. Overall survival (OS), progression-free survival (PFS), local tumor response, and adverse events (AEs) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…To reduce tumor burden and improve u-HCC prognosis, various combination regimens, including systemic and locoregional therapies, are now used. Our previous study found that the ORR after triple therapy was 80.6% (TACE, lenvatinib, and Anti-PD-1 antibody immunotherapy) (13)(14)(15)(16)(17). Despite the triple therapy, several patients experienced disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce tumor burden and improve u-HCC prognosis, various combination regimens, including systemic and locoregional therapies, are now used. Our previous study found that the ORR after triple therapy was 80.6% (TACE, lenvatinib, and Anti-PD-1 antibody immunotherapy) (13)(14)(15)(16)(17). Despite the triple therapy, several patients experienced disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…8,[12][13][14][15][16] Inspiringly, recent trials have proven striking efficacy of lenvatinib plus PD-1 inhibitors in patients with unresectable HCC. 8,15,16 Although there was insufficient evidence that the addition of PD-1 inhibitor to lenvatinib was superior to lenvatinib monotherapy, some retrospective studies, 6,[34][35][36][37][38] including ours, have shown that Len-TACE in combination with PD-1 inhibitor conferred improved response rate and survivals over Len-TACE for advanced HCC. In the present study, with the triple treatment of Len-Sin-TACE, remarkable clinical benefits in ORR, PFS and OS were achieved despite the extensive tumour burden on the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Among cancers, uHCC has one of the worst prognoses due to drug resistance, frequent recurrence, and metastasis [30]. Recently, a new combination strategy combining TACE + TKIs + ICIs has shown promising results, but not all patients benefit, and the high cost can be a significant concern [13,15]. Therefore, it is important to identify the patients who are most likely to benefit from this combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies demonstrated that incomplete embolization could cause an increase in programmed cell death ligand 1 and vascular endothelial growth factor (VEGF) [11,12] levels. Thus, many studies have focused on the combination of tailored tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) plus TACE (TACE + TKIs + ICIs), demonstrating significantly higher tumor response and survival benefits [13][14][15]. Some studies have shown that inflammation is involved in the development and progression of HCC [16,17].…”
Section: Introductionmentioning
confidence: 99%